Unexpected Huge Prevalence of Intracardiac Extension of Wilms Tumor-A Single Center Experience from a Ugandan Hospital - Massimo Mapelli; Paola Zagni; Roberto Ferrara; Valeria Calbi; Irene Mattavelli; Manuela Muratori; Jackson Kansiime; Cyprian Opira; Piergiuseppe Agostoni (MDPI AG, 2022)
Wilms tumor (WT) is the most common primary renal malignancy in young children. WT vascular extension to the inferior vena cava (IVC) occurs in 4-10% of cases and can reach the right atrium (RA) in 1%. Data on WT clinical presentation and outcome in developing countries are limited. The aim of the present study is to describe the prevalence of intracardiac extension in a consecutive population of WT patients observed in a large non-profit Ugandan hospital. A total of 16 patients with a histological diagnosis of 29 WT were screened in a 6-month period. Patient n°2, a 3 y/o child, presented with a 3-week history of abdominal distension, difficulty in breathing, and swelling of the lower limbs. A cardiovascular system exam showed rhythmic heart sounds, a heart rate of 110 beats per minute, and a pansystolic murmur on the tricuspid area; the abdomen was grossly distended with a palpable mass in the right flank, hepatomegaly, and splenomegaly. An abdomen ultrasound showed an intra-abdominal tumor, involving the right kidney and the liver and extended to the IVC. An ultrasound guided biopsy showed a picture consistent with WT. Cardiac echo showed a huge, mobile, cardiac mass attached to the right side of the interatrial septum, involving the tricuspid valve annulus, causing a "functional" tricuspid stenosis. The patient died of cardiogenic shock 7 days after admission. Patient n°3, a 3 y/o child, presented with analogue symptoms and the same diagnosis. The cardiac echo showed a round mass in the RA. Thirteen more patients were screened with cardiac echo, showing a normal heart picture. In our limited series, we found WT cardiac extension in three patients over 16 (19%). Cardiac echo performed routinely can lead to a better staging, prognostic, and therapeutic assessment. In our setting, the intra-cardiac extension could be more frequent than previously reported and might have prognostic implications.